Pengaruh Manajemen Konflik Peran Ganda, Pelatihan, Kesehatan dan Keselamatan Kerja Terhadap Perawat Wanita (Studi Kasus di RSUD BLAMBANGAN Banyuwangi) - Althof Sandi Ikmal Huda; Dewi Prihatini; Hadi Paramu (UPT Penerbitan Universitas Jember, 2019)
This study aims to identify and analyze the influence of work-family conflict management, training, health and safety on the performance of female nurses in RSUD BLAMBANGAN Banyuwangi. This study uses primary data obtained from respondents' answers on the questionnaires used in the study. Method of data analysis using Descriptive Statistics, Instrument Test, Classical Assumption Test and Hypothesis Test consisted of Multiple Linear Regression Analysis, T test, and F Test. The result of the research shows that the work-family conflict management, training, health and safety have positive and significant influence on the performance of female nurses in RSUD BLAMBANGAN Banyuwangi. This leads to better work-family conflict management , health and safety coach will improve the performance of female nurses at BLAMBANGAN Banyuwangi Hospital. Keywords: Work-Family Conflict Management, Training, Health and Safety, Performance.